Implementation of the “Aku Suka Menolong” Program for Improving Children Prosocial Behavior in Kalisapu Village Tegal - Dwi Kencana Wulan; Fitri Lestari Issom; Vinna Ramadhany Sy (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2020)
“Aku Suka Menolong” is a community service program that focuses on improving the prosocial behavior children in school age at Desa Kalisapu Slawi, Tegal Central Java. This program has 3 fun activities, first acitivity is the movie session with the main theme is about helping each other, then second activity is a puppet show which tells the story about helping then the third is giving the reward for the responden who practices prosocial behavior in everyday life. As an evaluation of effectiveness of the program, we gave a quationaire to gathered data about the prosocial behavior of the respondents, as the result we know that 80,65% respondent is classified to high score and 19,35% classified to low in prosocial behavior